An overview of downhill esophageal varices: a challenge for medical practice - Donghong Wang; Zhibin Ma (Annals of Medicine)
Objectives Unlike the commonly seen uphill esophageal varices in clinical practice, downhill esophageal varices are caused by obstruction of the superior vena cava and azygous venous system. The predominant causes of downhill esophageal varices are hemodialysis in end-stage renal disease patients and mediastinal malignancies. The cornerstone of the treatment for downhill esophageal varices is to address the underlying primary causes. Without this, patients may suffer from recurrent bleeding, and the bleeding can be fatal.Methods This review is primarily summarized through previous case reports. Meanwhile, it emphasizes the significance of case reports.Results Clinicians should be conscious that esophageal varices are not necessarily caused by liver cirrhosis or non-cirrhotic portal hypertension.Conclusions Specifically, when varices are only observed in the upper and middle esophagus, and the patient presents with evidence of superior vena cava obstruction, clinicians should be particularly vigilant for downhill esophageal varices. Moreover, a thorough investigation and definitive treatment of the underlying primary causes should be implemented.